2004
DOI: 10.1002/eji.200425309
|View full text |Cite
|
Sign up to set email alerts
|

Frontline: Peripheral priming of alloreactive T cells by the direct pathway of allorecognition

Abstract: Recent studies, though controversial, have suggested that secondary lymphoid organs may not constitute an essential site for the initiation of immune responses to transplant antigens. However, this issue has never been examined in the context of direct and indirect allorecognition. Here, we characterized immune responses arising in draining lymph nodes and skin allografts, in a murine model based on a single T cell clonotype where these two pathways can be independently studied. In this model, graft rejection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Indirect presentation has become increasingly appreciated as an important adjunct pathway in transplant allorecognition and in the case of skin grafts is sufficient to mediate rejection in the absence of direct presentation (5,7,(40)(41)(42)(43). Our results suggest that 2 additional mechanisms may therefore be important for insuring fetomaternal tolerance.…”
Section: Figurementioning
confidence: 69%
“…Indirect presentation has become increasingly appreciated as an important adjunct pathway in transplant allorecognition and in the case of skin grafts is sufficient to mediate rejection in the absence of direct presentation (5,7,(40)(41)(42)(43). Our results suggest that 2 additional mechanisms may therefore be important for insuring fetomaternal tolerance.…”
Section: Figurementioning
confidence: 69%
“…Recently, this route of activation of T cells reactive to alloantigen by the direct pathway has been called into question (29). Baratin et al (29) postulated that CD4 ϩ T cells that recognize alloantigen via the direct pathway were initially activated within the skin graft itself as they found little evidence of peripheral T cell priming.…”
Section: Discussionmentioning
confidence: 99%
“…Baratin et al (29) postulated that CD4 ϩ T cells that recognize alloantigen via the direct pathway were initially activated within the skin graft itself as they found little evidence of peripheral T cell priming. This result is in clear contrast to the data presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Using a unique model of TCR Tg mice (2.102Tg mice), which allows us to study independently the two pathways of allorecognition during skin graft, we have previously shown that the same 2.102Tg alloreactive CD4 + T cells were able to initiate graft rejection by both pathways (19). In this model, the kinetics of rejection were similar, although the initiation of alloreactive responses seems to occur earlier in the direct pathway, suggesting that tolerance mechanisms were operational in this pathway.…”
Section: Resultsmentioning
confidence: 99%